Поселення заключного періоду доби бронзи поблизу м. Зимогір’я в долині р. Лугані - Пробийголова, О.C. (Археологія і давня історія України, 2021)
У статті публікуються результати досліджень
поселення доби бронзи поблизу м. Зимогір’я в долині
р. Лугань. Добрий стан збереженості кам’яних
стін споруд та чітко простежені будівельні етапи
роблять отримані дані важливим джерелом для
вивчення доби пізньої бронзи регіону. Матеріали
поселення демонструють зміни в техніці кам’яної
кладки, форми споруд, керамічного посуду протягом заключного періоду бронзового віку. This article is devoted to the publication of the results
of excavations of the Late Bronze Age settlement
Zymogiria 4 in the basin of the Lugan river. The indication
of the culture is a debatable question that has
led to the involvement of habitations in to different
archeological cultures: bilozerka, Srubnaya, boguslavbilozerka,
ivanovka, otradnenska cultures. Observation
of the inheritances of the population of the Berezhnovka-
Maevka Srubnaya culture and the population of
the Final Bronze Age is proceed with materials from
the settlement. Problem of vagueness criteria for the
identification post-Zrubna settlements and their clear
extraction from Berezhnovka-Maevka Zrubna culture
settlements necessitated the importance of research
according to the new sources. The problem of the identification
of the post-Zrubna horisont will be solved
with Late Bronze Age settlement Zymogiria 4 stratigraphy
observation. Analysis of the stratigraphic horisonts
enables to extract the horisont of the late stage
Berezhnovka-Maevka Zrubna culture and horisont
post-Zrubna settlements. Presence of the periodization
for burials Berezhnovka-Maevka Zrubna culture give
possibility of the synchronization with settlements.
The system of the settlement placement, organization
of the inner space, traditions of the house building continue
the line of development the Berezhnovka-Maevka
Zrubna culture. At the same time, masonry wall technique
of the Final Bronze Age horizon changes, pottery
from the Final Bronze Age horizon of the settlement
has its own characteristics, which are different from
Berezhnovka-Maevka Zrubna culture. The new form
of vessels are appearing, the ornamentation changes.
New stone objects appear, that was not present in previous
period: whetstone with tray or hole for hanging.
In this work is made an attempt to separate the horizone
of the Final Bronze Age of Zymogiria 4 settlement
from the Berezhnovka-Maevka Zrubna culture horizones,
which have many common features.